Effects of Wx and Its Interaction With SSIII-2 on Rice Eating and Cooking Qualities - Yang, Bowen; Xu, Shunju; Xu, Liang; You, Hui; Xiang, Xunchao (Frontiers in Plant Science, 2018)
Wx gene, which encodes the granule-bound starch synthase (GBSS), play a key role on determining rice eating and cooking qualities (ECQs). SSIII-2 (SSIIIa) is one of the soluble starch synthases, which is responsible for the synthesis of long chain of branched starch. In order to investigate effects of Wx and its interaction with SSIII-2 on grain ECQs, we set up a population came from a hybrid combination as materials, identifying genotype of SSIII-2 and the single nucleotide polymorphism (SNP) on intron1, exon6, exon10 of Wx, measuring its physicochemical indicators and RVA profile characteristics. Results showed the effects of SSIII-2 on rice quality were different under the background of different Wx alleles. There were no significant differences among different SSIII-2 alleles under the background of Wxa. However, there were significant differences under the background of Wxb. Effect of SSIII-2 might be masked by the massive synthesis of GBSS under Wxa, which was the dominant factor controlling the rice quality and have dominant epistasis to SSIII-2. AAC was majorly controlled by In1G/T and Ex10C/T regulated rice GC. The combined effects of three SNPs had significant influence on whole ECQs and RVA profile parameters except for GT. In1T-Ex6A-Ex10C and In1T-Ex6A-Ex10T were classified as low AAC type. TT-AA-CC and TT-AA-TT had low AAC and soft GC. Combined effects of different SNPs of Wx are very important for rice quality breeding.